ALAT BANTU TRUK ANGKUTAN KAYU UNTUK MENGURANGI SELIP RODA PADA JALAN HUTAN TANPA PERKERASAN - Yuniawati; Dulsalam; Maman Mansyur Idris; Sona Suhartana; Sukadaryati (Jurnal Penelitian Hasil Hutan, 2015)
Timber hauling has a main goal to remove timber from forestland to the wood processing industry or directly to consumers. The hauling should be managed efficiently, so that the smooth running of transport should be prioritized. Slip is a serious obstacle that must be anticipated when hauling using trucks. It can reduce labor productivity and increase cost of hauling. The experiment was conducted in April 2014 in the RPH Cijogon, BKPH Tanggeung, Cianjur KPH Perhutani Unit III West Java and Banten. The purpose of research is to find out the use of auxiliary tools for reducing road slip in teak land hauling. The auxiliary tools were designed and manufactured in the workshop. The tools were then applied on the truck wheels in various slopes of slip. Results showed that: the average slip on slope class 0-8%, 9-15% and 16-25 % respectively 3.24 %, 6.11% and 7.58 % with each traction coefficient of 0.59, 0.44 and 0.36. The productivity of teak logs using the tools on slope class 0-8 %, 9-15% and 16-25% respectively 92.02 m³/km/hour, 89.07 m³/km/hour and 83.59 m³/km/hour and production, costs of corresponding teak logs are Rp 2640.01/m³/km, Rp 2737.92/m³/km and Rp 2917.27/m³/km.